Dynamical behavior of digitations state in Faraday waves with a viscoelastic fluid - Cabeza, Cecilia (2006)
Parametrically excited surface waves, well known as Faraday waves, are studied when finger structures are generated on the free surface. In this state, the surface breaks and ejects droplets from wave peaks when the applied force exceeds an acceleration threshold. In this work, both the chaotic and turbulent bifurcation behaviors of Faraday surface waves have been intensively studied and many different transitions have been examined and described. The spatial and temporal finger distribution is studied as a function of external acceleration.